Inhibition of Chloride Intracellular Channel 1 (CLIC1) as Biguanide Class-Effect to Impair Human Glioblastoma Stem Cell Viability - Barbieri, Federica; Würth, Roberto; Pattarozzi, Alessandra; Verduci, Ivan; Mazzola, Chiara; Cattaneo, Maria G.; Tonelli, Michele; Solari, Agnese; Bajetto, Adriana; Daga, Antonio; Vicentini, Lucia M.; Mazzanti, Michele; et al. (Frontiers in Pharmacology, 2018)
The antidiabetic biguanide metformin exerts antiproliferative effects in different solid tumors. However, during preclinical studies, metformin concentrations required to induce cell growth arrest were invariably within the mM range, thus difficult to translate in a clinical setting. Consequently, the search for more potent metformin derivatives is a current goal for new drug development. Although several cell-specific intracellular mechanisms contribute to the anti-tumor activity of metformin, the inhibition of the chloride intracellular channel 1 activity (CLIC1) at G1/S transition is a key events in metformin antiproliferative effect in glioblastoma stem cells (GSCs). Here we tested several known biguanide-related drugs for the ability to affect glioblastoma (but not normal) stem cell viability, and in particular: phenformin, a withdrawn antidiabetic drug; moroxydine, a former antiviral agent; and proguanil, an antimalarial compound, all of them possessing a linear biguanide structure as metformin; moreover, we evaluated cycloguanil, the active form of proguanil, characterized by a cyclized biguanide moiety. All these drugs caused a significant impairment of GSC proliferation, invasiveness, and self-renewal reaching IC50 values significantly lower than metformin, (range 0.054 and 0.53 mM vs. 9.4 mM of metformin). All biguanides inhibited CLIC1-mediated ion current, showing the same potency observed in the antiproliferative effects, with the exception of proguanil which was ineffective. These effects were specific for GSCs, since no (or little) cytotoxicity was observed in normal umbilical cord mesenchymal stem cells, whose viability was not affected by metformin and moroxydine, while cycloguanil and phenformin induced toxicity only at much higher concentrations than required to reduce GSC proliferation or invasiveness. Conversely, proguanil was highly cytotoxic also for normal mesenchymal stem cells. In conclusion, the inhibition of CLIC1 activity represents a biguanide class-effect to impair GSC viability, invasiveness, and self-renewal, although dissimilarities among different drugs were observed as far as potency, efficacy and selectivity as CLIC1 inhibitors. Being CLIC1 constitutively active in GSCs, this feature is relevant to grant the molecules with high specificity toward GSCs while sparing normal cells. These results could represent the basis for the development of novel biguanide-structured molecules, characterized by high antitumor efficacy and safe toxicological profile.